1998
DOI: 10.5326/15473317-34-5-377
|View full text |Cite
|
Sign up to set email alerts
|

Realignment of a seventh lumbar vertebral fracture/luxation using a Senn retractor in two puppies

Abstract: Two puppies, each with fractures of the seventh lumbar (L7) vertebra, had their vertebral canals aligned surgically with the aid of a Senn retractor. The retractor was used to provide leverage during vertebral manipulations. Surgical fixation was achieved using Steinmann pins and polymethylmethacrylate. Both puppies were improved immediately after surgery and were clinically normal six months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
0
13
0
2
Order By: Relevance
“…Lumbosacral fracture–luxations are most commonly seen in younger dogs as a result of motor vehicle trauma 10,13,14 . It has been suggested that the lumbosacral joint is prone to injury because of the relationship of the mobile caudal lumbar spine to the relatively fixed sacrum 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Lumbosacral fracture–luxations are most commonly seen in younger dogs as a result of motor vehicle trauma 10,13,14 . It has been suggested that the lumbosacral joint is prone to injury because of the relationship of the mobile caudal lumbar spine to the relatively fixed sacrum 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Spinal fractures are relatively common in dogs and are usually the result of motor vehicle accidents (1)(2)(3)(4). Fractures of the seventh lumbar (L7) vertebra generally result from direct flexional and compression trauma to the hindquarters.…”
Section: Introductionmentioning
confidence: 99%
“…We found 466 records in the database searching from 1975 to June 2021. After the removal of duplicates, we screened 432 records, from which we reviewed 28 full-text documents, and finally included eight papers [ 5 , 10 , 11 , 12 , 13 , 16 , 19 , 20 ]. Later, we searched records from the reference lists of initially included studies, and found one article that fulfilled our inclusion criteria [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first published report of fractures of L7 in the dog was in 1975 [ 7 ], and, in the last 46 years, different techniques have been described to stabilize these fractures [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The clinical presentation and the outcomes related to these techniques have been reported but in small case series.…”
Section: Introductionmentioning
confidence: 99%